x*x*x-3*x*x-3*x-1=0

Simple and best practice solution for x*x*x-3*x*x-3*x-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*x*x-3*x*x-3*x-1=0 equation:


Simplifying
x * x * x + -3x * x + -3x + -1 = 0

Multiply x * x
x2 * x + -3x * x + -3x + -1 = 0

Multiply x2 * x
x3 + -3x * x + -3x + -1 = 0

Multiply x * x
x3 + -3x2 + -3x + -1 = 0

Reorder the terms:
-1 + -3x + -3x2 + x3 = 0

Solving
-1 + -3x + -3x2 + x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| -x/6=3/9 | | -x-12+5x=9-10x+7 | | X+(140-g)+(20+g)+g=290 | | N/-10=3 | | 7u+47=3(u+9) | | X/3=1.8 | | 9-7=8 | | 3x-2(x-5)=7x-4(2x+1) | | 35x-5=x+17 | | -x/6=6/9 | | 5(w-2)-7w=-30 | | x^2-8x+13=-4 | | 2x^7+18x^6+36x^5=0 | | X+22=35x | | 18+19m+m^2=0 | | 1/0*190340 | | -3/8=x/24 | | r^2-6r-83=-10 | | -3n+12-n=40+8 | | 7/10-7=7 | | X/10=7/10 | | v^2-12v+34=-6 | | 2+6x-2x=-8+2x | | A^4-2a^2-35=0 | | 2x+3=3x+-2 | | 81r^2-49= | | 17=kg-2 | | 9x^2+8= | | -8x-(-5)=12x-(-85) | | -3x-(-8)=-9x-28 | | 2x-6=24+3x | | 8x-12=-8x-140 |

Equations solver categories